Navigating gallstones in pregnancy: a case of surgical precision and obstetric vigilance - K., Devapriya; Wills, Vinitha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Gallstone disease during pregnancy poses clinical challenges due to altered physiology and concerns over fetal safety. We present the case of a 28-year-old primigravida who had undergone endoscopic retrograde cholangiopancreatography (ERCP) with biliary stenting for choledocholithiasis prior to conception. She remained asymptomatic during early pregnancy, with normal liver function and no signs of cholecystitis on magnetic resonance cholangiopancreatography (MRCP). After multidisciplinary evaluation, laparoscopic cholecystectomy was performed during the second trimester using fetal-safe anaesthetic techniques and open abdominal access. The procedure was uneventful, and recovery was smooth. She later delivered a healthy term infant via spontaneous vaginal delivery at 37 weeks. This case supports the growing evidence that laparoscopic cholecystectomy, when carefully timed and executed, is a safe and effective treatment for gallstone disease in pregnancy.